Climate Change Projected to Increase Rates of Background Tree Mortality Across Eastern North America - Jiejie Wang; Anthony R. Taylor; Mathieu Bouchard; Loïc D'Orangeville (Global Change Biology, 2026)
Tree mortality patterns play a central role in forest health, terrestrial carbon dynamics, and biodiversity conservation. While changes in tree mortality patterns to recent climate anomalies have been documented, the effects of climate change on ambient or “background” mortality rates in the absence of severe disturbance agents remains poorly understood. Here, we applied a machine learning approach to a large dataset of 24,576 forest permanent sample plots distributed across Canada and the United States, spanning 28.1°C in mean annual temperature and 1743.5 mm in annual precipitation, to study and predict the effects of climate on background mortality for nine of the most abundant tree species in eastern North America. We developed species‐specific climate‐mortality models while controlling for the interactive effects of stand development processes, CO 2 , and atmospheric pollutant SO 4 . We found that temperature ranked among the three strongest predictors of mortality rates and that warmer temperatures led to higher background tree mortality for most species. Furthermore, we predicted notable increases in tree mortality rates along the southern portions of species' ranges in response to future warming. On average, mortality rates are predicted to rise by 0.2%–0.7%·year −1 for five of the nine species under SSP2‐4.5 by mid‐century (2041–2070). By examining climate‐driven variation in background tree mortality at the continental scale, our study provides valuable insight on future forest dynamics under climate change.

Persistence With Botulinum Neurotoxin Type A and Factors Associated With Discontinuation: A Retrospective Cohort Study - Michael Wainberg; Jinming Zhang; Simon Page; Nivedita Rangarajan; Sandeep Kumar; Jonathan Bouchard; Amandeep Mann; Mathieu Beneteau; Billie Schultz (Toxicon, 2026)

Correction factors for large-scale greenhouse gas assessment from pulp and paper mill sludge landfill sites - Ranieri Ribeiro Paula; Mathieu Cusson; Normand Bertrand; Sylvie Bouchard; Martin H. Chantigny; Julie Lemieux; Emna Marouani; Claude Villeneuve; Patrick Faubert (Waste Management, 2024)

Above- and belowground carbon stocks under differing silvicultural scenarios - Anne Ola; William Devos; Mathieu Bouchard; Marc J. Mazerolle; Patricia Raymond; Alison D. Munson (Forest Ecology and Management, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Desired REgeneration through Assisted Migration (DREAM): Implementing a research framework for climate-adaptive silviculture - Alejandro A. Royo; Patricia Raymond; Christel C. Kern; Bryce T. Adams; Dustin Bronson; Emilie Champagne; Daniel Dumais; Eric Gustafson; Paula E. Marquardt; Amanda M. McGraw; Jessica R. Miesel; Alison D. Munson; et al. (Forest Ecology and Management, 2023)

Multi‐model projections of tree species performance in Quebec, Canada under future climate change - Yan Boulanger; Jesus Pascual; Mathieu Bouchard; Loïc D'Orangeville; Catherine Périé; Martin P. Girardin (Global Change Biology, 2022)
Many modelling approaches have been developed to project climate change impacts on forests. By analysing ‘comparable’ yet distinct variables (e.g. productivity, growth, dominance, biomass, etc.) through different structures, parameterizations and assumptions, models can yield different outcomes to rather similar initial questions. This variability can lead to some confusion for forest managers when developing strategies to adapt forest management to climate change. In this study, we standardized results from seven different models (Habitat suitability, trGam, StandLEAP, Quebec Landscape Dynamics, PICUS, LANDIS‐II and LPJ‐LMfire) to provide a simple and comprehensive assessment of the uncertainty and consensus in future performance (decline, status quo, improvement) for six tree species in Quebec under two radiative forcing scenarios (RCP 4.5 and RCP 8.5). Despite a large diversity of model types, we found a high level of agreement (73.1%) in projected species' performance across species, regions, scenarios and time periods. Low agreements in model outcomes resulted from small dissensions among models. Model agreement was much higher for cold‐tolerant species (up to 99.9%), especially in southernmost forest regions and under RCP 8.5, indicating that these species are especially sensitive to increased climate forcing in the southern part of their distribution range. Lower agreement was found for thermophilous species (sugar maple, yellow birch) in boreal regions under RCP 8.5 mostly as a result of the way the different models are handling natural disturbances (e.g. wildfires) and lags in the response of populations (forest inertia or migration capability) to climate change. Agreement was slightly higher under high anthropogenic climate forcing, suggesting that important thresholds in species‐specific performance might be crossed if radiative forcing reach values as high as those projected under RCP 8.5. We expect that strong agreement among models despite their different assumptions, predictors and structure should inspire the development of forest management strategies to be better adapted to climate change.

Pelagic production and the recruitment of juvenile polar cod Boreogadus saida in Canadian Arctic seas - Mathieu LeBlanc; Maxime Geoffroy; Caroline Bouchard; Stéphane Gauthier; Andrew Majewski; James D. Reist; Louis Fortier (Polar Biology, 2020)
Previous work found that an earlier ice breakup favors the recruitment of juvenile polar cod ( Boreogadus saida ) by enabling early hatchers to survive and reach a large size by late summer thanks to a long growth season. We tested the hypothesis that, in addition to a long growth season, an earlier ice breakup provides superior feeding conditions for young polar cod by enhancing microalgal and zooplankton production over the summer months. Ice cover and surface chlorophyll a were derived from satellite observations, and zooplankton and juvenile cod biomass were estimated by hydroacoustics in ten regions of the Canadian Arctic over a period of 11 years. Earlier breakups resulted in earlier phytoplankton blooms. Zooplankton backscatter in August increased with earlier breakup and bloom, and plateaued at chlorophyll a > 1 mg m −3 . Juvenile cod biomass in August increased with an earlier breakup, and plateaued at a zooplankton backscatter > 5 m 2 nmi −2 , supporting the hypothesis that higher food availability promotes the growth and survival of age-0 fish in years of early ice melt. However, there was little evidence that late summer biomass of either zooplankton or age-0 polar cod benefitted from ice breakup occurring prior to June. On average, zooplankton standing stock was similar in the Southern Beaufort Sea and the North Water-Lancaster Sound polynya complex, but juvenile cod biomass was higher in the Beaufort Sea. Intense avian predation could explain the lower biomass of juvenile cod in the polynya complex, confirming its reputation as a biological hotspot for energy transfer to higher trophic levels.

Warming counteracts defoliation‐induced mismatch by increasing herbivore‐plant phenological synchrony - Ping Ren; Valérie Néron; Sergio Rossi; Eryuan Liang; Mathieu Bouchard; Annie Deslauriers (Global Change Biology, 2020)
Climate change is altering phenology; however, the magnitude of this change varies among taxa. Compared with phenological mismatch between plants and herbivores, synchronization due to climate has been less explored, despite its potential implications for trophic interactions. The earlier budburst induced by defoliation is a phenological strategy for plants against herbivores. Here, we tested whether warming can counteract defoliation‐induced mismatch by increasing herbivore‐plant phenological synchrony. We compared the larval phenology of spruce budworm and budburst in balsam fir, black spruce, and white spruce saplings subjected to defoliation in a controlled environment at temperatures of 12, 17, and 22°C. Budburst in defoliated saplings occurred 6–24 days earlier than in the controls, thus mismatching needle development from larval feeding. This mismatch decreased to only 3–7 days, however, when temperatures warmed by 5 and 10°C, leading to a resynchronization of the host with spruce budworm larvae. The increasing synchrony under warming counteracts the defoliation‐induced mismatch, disrupting trophic interactions and energy flow between forest ecosystem and insect populations. Our results suggest that the predicted warming may improve food quality and provide better growth conditions for larval development, thus promoting longer or more intense insect outbreaks in the future.

Do natural enemies explain fluctuations in low‐density spruce budworm populations? - Mathieu Bouchard; Véronique Martel; Jacques Régnière; Pierre Therrien; David Laginha Pinto Correia (Ecology, 2018)
Understanding the causal pathways through which forest insect outbreaks are triggered is important for resource managers. However, detailed population dynamics studies are hard to conduct in low‐density, pre‐outbreak populations because the insects are difficult to sample in sufficient numbers. Using laboratory‐raised larvae installed in the field across a 1,000 km east–west gradient in Québec (Canada) over an 11‐yr period, we examined if parasitism and predation were likely to explain fluctuations in low‐density spruce budworm ( Choristoneura fumiferana ; SBW) populations. Parasitism rates by the two main larval parasitoid species, Elachertus cacoeciae and Tranosema rostrale , peaked during different years. This suggests that temporal fluctuations in overall parasitism were partly buffered by compensatory dynamics among parasitoid species. Still, spatial covariance analyses indicate that the residual interannual variation in parasitism rates was substantial and correlated over large distances (up to 700 km). On the other hand, interannual variation in predation rates was not spatially correlated. Piecewise structural equation models indicate that temporal variation in parasitism and predation does not influence temporal variation in wild SBW abundance. Spatially, however, SBWs installed in warmer locations tended to show higher parasitism rates, and these higher rates correlated with lower wild SBW population levels. Overall, the results indicate that large‐scale drops in parasitism occur and could potentially contribute to SBW population increases. However, during the period covered by this study, other factors such as direct effects of weather on SBW larval development or indirect effects through host tree physiology or phenology were more likely to explain large‐scale variation in wild SBW populations.

Using biodiversity deconstruction to disentangle assembly and diversity dynamics of understorey plants along post‐fire succession in boreal forest - Ermias T. Azeria; Mathieu Bouchard; David Pothier; Daniel Fortin; Christian Hébert (Global Ecology and Biogeography, 2011)
Aim The study aims to decipher the co‐occurrence of understorey plant assemblages and, accordingly, to identify a set of species groups (diversity deconstruction) to better understand the multiple causal processes underlying post‐fire succession and diversity patterns in boreal forest. Location North‐eastern Canadian boreal forest (49°07′–51°44′ N; 70°13′–65°15′ W). Methods Data on understorey plant communities and habitat factors were collected from 1097 plots. Species co‐occurrence was analysed using null model analysis. We derive species groups (i.e. biodiversity deconstruction) using the strength of pairwise species co‐occurrences after accounting for random expectation under a null model and cluster analyses. We examine the influence of a set of spatiotemporal environmental variables (overstorey composition, time‐since‐fire, spatial location and topography) on richness of species groups using Bayesian model averaging, and their relative influence through hierarchical partitioning of variance. Results Understorey plant assemblages were highly structured, with co‐occurrence‐based classification providing species groups that were coherently aggregated within, but variably segregated between, species groups. Group richness models indicate both common and distinct responses to factors affecting plant succession. For example, Group 2 (e.g. Rhododendron groenlandicum and Cladina rangiferina ) showed concurrent contrasting responses to overstorey composition and was strongly segregated from Groups 3 (e.g. Clintonia borealis and Maianthenum canadense ) and 4 (e.g. Epilobium angustifolium and Alnus rugosa ). Groups 3 and 4 showed partial similarity, but they differed in their response to time‐since‐fire, drainage and latitude, which were more important for Group 1 (e.g. Ptilium crista‐castrensis and Empetrum nigrum ). A single successional model based on total richness masked crucial group‐level relationships with factors that we examined, such as latitude. Main conclusions By demonstrating the co‐occurrence structure and linking to causal factors, the results from this study characterize both common and distinct responses of understorey plants to biophysical attributes of sites, and potential interspecific interactions, behind non‐random assemblage structure during post‐fire succession. A biodiversity deconstruction approach could offer a concise and explicit framework to gain a better understanding of the complex assembly of ecological communities during succession.

Biological monitoring of exposure to organophosphate pesticides in children living in peri-urban areas of the Province of Quebec, Canada - Mathieu Valcke; Onil Samuel; Michèle Bouchard; Pierre Dumas; Denis Belleville; Claude Tremblay (International Archives of Occupational and Environmental Health, 2006)